Engineering integrative vectors based on bacteriophage site specific recombination mechanism for heterologous expression of secreted and surface-anchored protein in Lactococcus lactis - Koko, Innanurdiani (2019)
Bacterial integrating system allows integration of foreign DNA into bacterial host chromosome enabling stable expression of foreign gene for recombinant protein production. In this study, integrative expression vectors for secretion and surface display of heterologous protein in Lactococcus lactis have been successfully constructed based on the site-specific recombination mechanism, of temperate lactococcal phage TP901-1. Two variations of integrative vectors were constructed, denoted pS1-4, and pSD1-4, which allows the heterologous protein to be secreted into the extracellular environment or surface displayed on L. lactis, respectively. The integrative vectors composed of (i) P170 autoinducible promoter or PnisA inducible promoter, (ii) multiple cloning sites (MCS), (iii) TP901-1 bacteriophage attachment site, attP, (iv) signal peptide-encoding sequence USP45 fused with LEISSTCDA propeptide or SPK1 signal peptide for extracellular targeting, and (v) 344 amino acids of proteinase anchor domain (PrtP344) for surface display application. A helper plasmid harbouring int gene, pNZint was also constructed to facilitate plasmid integration into the genome. A staphylococcal nuclease reporter gene was cloned into each of the constructed integrative vectors which were then successfully integrated into the L. lactis genome. Toluidine blue O-DNA assay and immunofluorescence microscopy data proved that the expressed nuclease was able to be secreted or anchored on the L. lactis cell wall. From the findings, signal peptide SPK1 was shown to be superior over USP45 in the secretion of Nuc, even though the USP45 was fused with LEISSTCDA propeptide which reportedly could enhance protein secretion. Meanwhile, the expression of Nuc showed that integrative vectors driven by P170 promoter have comparable strength to PnisA promoter. However, the combination of P170 with USP45-LEISSTCDA fusion performed significantly worse than the other constructs for surface display of Nuc. Therefore, these newly constructed synthetic integrative vectors can be applied for the secretion and surface display of heterologous protein in L. lactis for research or industrial purposes where strong and weak stable expression vectors are required.